Odpowiedzi

2009-11-25T18:57:05+01:00
A
5y=2 / :5
x+y=2⅖

y=⅖
x+⅖=2⅖

y=⅖
x=2
B
y=0
x=-6
C
a=b
2a+b=9

2a+a=9
3a=9
a=3
D
u=4v
5u-v=10

5*4v-v=10
19v=10/:19

v=¹⁰/₁₉
u=4*¹⁰/₁₉
u=⁴⁰/₁₉
u=2 i2dziewietnaste

E
3r=s
3r+s=24

3r=s
3r+3r=24

6r=24 /:6
r=4
s=3*4

r=4
s=12
2009-11-25T19:04:31+01:00
A)
(5y=2
(x+y=2 2/5

5y=2
x+y=12/5 |*(-5)

5y=2
-5x-5y=-12

-5x=-10
x=2

5y=2
y=0,4



B)
(4y-x=6
(17y=0

y=0

4y-x=6
0-x=6

x=-6




C)
(a=b |*(-2)
(2a+b=9

-2a=-2b
2a+b=9

-b=9
b=-9

2a+b=9
2a-9=9

2a=18
a=9

D)
(u=4v
(5u-v=10

u=4v
5*4v-v=10

u=4v
20v-v=10

19v=10
v=10/19

u=4v
u=4*10/19

u=40/19



E)
(3r=s
(3r+s=24|*(-)

3r=s
3r+3r=24

3r=s
6r=24 |:6

r=4

3r=s
12=s